월악산에서의 물까치 Cyanopica cyana의 번식생태 및 개체군 변동에 관한 연구 - 오태훈(Tae-Hoon Oh); 백충렬(Chung-Ryul Baek); 이진희(Jin-Hee Yi); 정진우(Jin-Woo Jung); 염광석(Kang-Suk Youm); 조현준(Hyun-Jun Cho); 조삼래(Sam-Rae Cho) (한국조류학회지, 2010)
본 연구는 2005년 3월부터 2009년 10월까지 월악산(충북 제천시 한수면 덕주골 계곡)에 분포하는 물까치의 둥지 장소 선택, 개체수 변동, 성장률, 먹이 종류 등 번식생태 및 개체군 변동에 영향을 주는 방해 요인을 조사하여 분석하였다. 관찰된 개체수는 2005년 104개체, 2006년 63개체,2007년 107개체, 2008년 142개체, 2009년 205개체로 증가하는 경향을 보였다. 영소목은 특정수종을 선호하지 않고, 서식하는 지역의 식생을 이용하였다. 영소목의 수고는 12.79±1.98m이었고 참나무류를 주로 이용하였으며, 영소목에서의 둥지의 높이는 3.91±0.56m이었다. 둥지와 계곡과의거리는 20.90±12.17m였고, 과수원과의 거리는 41.83±11.74m이었다. 둥지 재료는 상수리나무, 갈참나무 등 주변의 작은 나뭇가지를 이용하였다. 번식시기는 4월 중순∼6월 초순경이며 한배산란수는 6.9±1.06개, 포란기간은 17.90±1.30일, 그리고 비동시 부화일수는 1.86±0.78일로 나타났다. 먹이는 양서류 및 파충류 그리고 곤충 등 동물성과 연한 식물 및 견과류 등을 먹는 잡식성으로 나타났다. 번식 실패의 주요인은 날씨와 먹이로 나타났다. 부화성공률은 90.82%, 이소성공률은88.30%, 번식성공률 80.19%로 다른 까마귀과 조류에 비해 높았다. 물까치는 잡식성이며, 무리생활을 하여 포식자에 대한 위협에 대처하고 있으며, 최근 천적 및 경쟁종이 감소하고 있어 연구대상 지역 일대에서 개체수가 늘어나고 있는 것으로 판단된다. We have researched population change, preference of nest tree and breeding ecology-growth rates, food materials, factors of disturbance-of Azure-winged Magpie’s Cyanopica cyana at Deok-ju valley, Worak Mountain, Chungcheongbuk-do, Korea from March, 2005 to October,2009. There were mountain streams, grasses, bushes and fruit trees which supply food to Azure-winged magpie. With these good environments, the number of Azure-winged magpie gradually increased 104 individuals in 2005, 63 individuals in 2006, 107 individuals in 2007, 142individuals in 2008 and 205 individuals in 2009. Azure-winged magpie made their nest in the Oak Community. This result suggested that Azure-winged magpie don't use specific trees. The height of nest tree was 12.79±1.98m. And the nest was positioned 3.91±0.56m from ground. The distance from nest to mountain stream was 20.90±12.17m and nest to orchard was 41.83±11.74m. The clutch size of Azure-winged magpie was 6.9±1.06. They lays its eggs during April to early of June and incubated for 17.90±1.30 days. The food materials was animals which includes insects,larva, amphibians, reptiles and plant materials like fruits and berries, etc. The hatching rate of Azure-winged magpie was 90.82%, fledgling rate was 88.30% and the rate of breeding success was 80.19%. The population of Azure-winged magpies are increasing because of the number of enemies are decreasing. And they defend enemy with another members of the community. KCI Citation Count: 3